Red cell transfusion in critical care: Could less be more? - Karki, Bipin; Maskay, Shirish Shakti; Mohammad, Ashad Shaheed; Neupane, Aryan (Journal of Nepalese Society of Critical Care Medicine, 2023)
Blood transfusion has a very important place in ancient medicine where it is associated with vitality. In the era of modern medicine, it still holds an important place. Critical events in the history led to the development of the physiological knowledge of blood flow and pathological processes associated with anemia. These still have a strong foothold in the practice of transfusion medicine which until very recently led physicians to liberally transfuse red blood cells to patients. However, the past few decades have revealed the darker side associated with transfusion of red blood cells. Recent evidences strongly suggest that the arbitrary transfusion triggers that had been historically set might have been too high, possibly causing unnecessary harm. Here, in this narrative review, the authors have tried to explore the evidences favoring lower transfusion threshold and without added adverse events thus supporting the notion – less is more.